Comparative Phylodynamics of HIV-1 Subtype B, Subtype C and CRF02_AG Epidemics Across Different Geographical Regions - Silva, Daiana Mir da (2018)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Rio de Janeiro, RJ, Brasil.